EKSISTENSI PASRAMAN DUKUH SULADRI DALAM PENGEMBANGAN KEARIFAN LOKAL BALI DI DESA ADAT BUNUTIN KABUPATEN BANGLI - I Gusti Made Putra Ambarajaya; Ni Wayan Arini; Ida Ayu Adi Armini (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the implementation, constraints, and implications of the Balinese local wisdom development program at Pasraman Dukuh Suladri, Bunutin Customary Village, Bangli Regency. As a non-formal education institution, Pasraman Dukuh Suladri plays a strategic role in preserving cultural and Hindu spiritual values amidst modernization. The research method used is qualitative with a phenomenological approach. Data was collected through in-depth interviews, non-participant observation, and document study, then analyzed using descriptive techniques. The results showed that Pasraman Dukuh Suladri implements four main programs: traditional music (tabuh) training, traditional dance training, making offering components (ngulat tipat), and Balinese language literacy. These programs function to maintain the social and cultural equilibrium of the local community. The constraints faced are internal, such as limited facilities, funding, and volunteer teachers, as well as external constraints like inconsistent student attendance due to parents' busy schedules. Accommodation efforts are made through the use of village facilities, funding proposals, and digital communication innovations. Implicatively, based on B.F. Skinner's behaviorism theory, this program forms the Pancasila Student Profile, strengthens character based on Tri Kaya Parisudha for the students, and solidifies the Customary Village's position as a fortress of local wisdom.